The Effect of Tourism Sector on Labor Absorption in Central Java 2018-2023 - Himmatus Suroyya; Retno Febriyastuti Widyawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
While tourism is a significant driver of regional economic growth, Indonesia's social and economic issues have not disappeared. Indonesia's population is growing rapidly, but job opportunities and human resource development are not keeping up. There is a serious issue brought on by this imbalance that requires attention.This study intends to assess the number of tourist destinations, visitors, hotel rooms employed in Central Java. The focus of the study includes three variables, namely, the influence of tourism objects, the number of visitors, and the availability of hotel rooms on labor absorption. Data from the Central Bureau of Statistics, the top 10 districts / cities with the highest number of visitors to tourism objects and events in Central Java in 2023 include Klaten Regency, Semarang, Banyumas, Magelang, Demak, Purbalingga, Kebumen, Jepara Regency, Surakarta and Semarang City. This study employs secondary data and a descriptive quantitative methodology. This study utilizes data from the Department of Youth, Sports, and Tourism and the Central Bureau of Statistics for the years 2018–2023.The data using panel data regression techniques, with the Fixed Effect Model (FEM) with the help of Eviews-12, to determine the connection between these variables. This finding indicates that the number of attractions and visitors have no meaningful impacton employment, while the availability of hotel rooms had a positive and significant impact. Increasing hotel capacity can create more employment opportunities in the tourism sector. These findings highlight the importance of strategic tourism development policies to maximize employment and improve the welfare of local communities. This study advances knowledge of the relationship between employment and tourism in Central Java and offers guidance to policymakers on how to promote the growth of sustainable tourism.